2021
DOI: 10.1111/bcp.15041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of colchicine in patients with coronary artery disease: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Inflammation plays a central role in the pathogenesis and clinical manifestations of atherosclerosis. Randomized controlled trials have investigated the potential benefit of colchicine in reducing cardiovascular (CV) events in patients with coronary artery disease (CAD) but produced conflicting results. The aim of this meta-analysis was to evaluate the efficacy and safety of colchicine in patients with CAD.Methods: We systematically searched selected electronic databases from inception until 10 December 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Thus, it was found that colchicine significantly reduces the risk of stroke in patients at high cardiovascular risk [34]. In the previously cited meta-analysis by Bytyçi et al [32] it was also shown that the use of colchicine reduced the risk of stroke (Fig. 2).…”
Section: Secondary Cardiovascular Prevention and In-stent Restenosismentioning
confidence: 85%
“…Thus, it was found that colchicine significantly reduces the risk of stroke in patients at high cardiovascular risk [34]. In the previously cited meta-analysis by Bytyçi et al [32] it was also shown that the use of colchicine reduced the risk of stroke (Fig. 2).…”
Section: Secondary Cardiovascular Prevention and In-stent Restenosismentioning
confidence: 85%
“…A recent systemic review and meta-analysis pooling data from 12 RCTs, similarly shows a lower risk of MACE, recurrent MI, and hospitalization due to CV events, but overall similar all-cause and CV mortality. 101 Based on these results, in the recent ESC Prevention Guidelines (2021), colchicine was indicated as a drug to reduce inflammation and a low dose (0.5 mg once daily) should be considered for the secondary prevention of CV disease, especially in high-risk patients. 102 Figure 1 details the presumed mechanisms by which the aforementioned medications act to reduce systemic inflammation, and local inflammation within atheromatous plaques.…”
Section: Evidence Of Pharmacological and Non-pharmacological Therapeu...mentioning
confidence: 99%
“…The central role of inflammation in the pathogenesis and clinical manifestation of atherosclerosis has also been confirmed by the reduction in coronary events by colchicine, an anti-inflammatory drug that reduces the inflammatory activity of leukocytes [ 70 , 71 ]. Moreover, in stable patients with previous myocardial infarction and persistent systemic inflammatory response, blocking the interleukin-6 activity directly using the monoclonal antibody canakinumab resulted in significant reduction in high-sensitivity CRP levels and incidence of subsequent CV events, without changes in low-density lipoprotein cholesterol [ 72 ].…”
Section: Recognised Underlying Mechanisms That Can Be Measured In Lab...mentioning
confidence: 99%